Untreated exstrophy-epispadias complex: outcomes of Indiana pouch and primary abdominal wall closure - Niraj Kumar; Avishek Mandal; Sandeep Kumar; Siddharth Yadav; Somanath Karmungikar; Pawan Vasudeva (African Journal of Urology)
Abstract Background We assessed the outcomes of adult patients with untreated exstrophy-epispadias complex who underwent Indiana continent catheterisable pouch type of urinary diversion along with primary closure of the abdominal wall utilizing the de-epithelised muscular coat of the vesical remnant. Methods This retrospective study analysed data between July 2019 and December 2023. All patients underwent a standard evaluation and surgical procedure and were followed up at 6 weeks, 3, 6 and 12 months and then annually. At each visit, renal function test and ultrasonography were performed and a 3 day CIC diary was obtained. The objective success was defined as complete diurnal and nocturnal continence with a pouch capacity of at least 300 ml, whereas the subjective success was defined as the Patient Global Impression of Improvement (PGI-I) score of 1 or 2 at 12 months post-surgery. Results A total of ten patients were included, and the mean operative time was 370 min, the mean blood loss was 400 ml and the mean hospital stay was 17 days. The overall complication rate was 40% and there was 1 Clavien IIIb complication. The mean duration of follow-up was 15.6 months and the mean maximum capacity of the pouch was 450 ml and the mean CIC frequency was 4.9 per day. The objective and subjective success rates were 100% and 100%, respectively. Conclusion Indiana pouch continent cutaneous urinary diversion is a feasible option with acceptable complication rates. It is a technically simpler procedure and obviates the need for extensive reconstructions and inter-departmental expertise and provides durable results.